Patient Satisfaction Level Concerning Dentistry Services during the COVID-19 Pandemic - Sandy, Nicholaus; Juliawati, Mita; Andayani, Lia H. (e-GiGi, 2022)
Abstract: Patient satisfaction is a comparison between the patient’s perception of the service received and their expectation before getting the service. The level of patient satisfaction is very important because it could be a measure of the success of a health care facility. The COVID-19 pandemic has an impact on patient satisfaction due to changes in the service flow. This study aimed to determine the level of patient satisfaction with dental services during the COVID-19 pandemic. This is an observational descriptive study with a cross sectional research design. The study was conducted by distributing the patient satisfaction questionnaire to 100 patients who received dental treatment at Puskesmas (Public Health Center) Kampung Sawah, Kecamatan Tanjung Karang Timur, Bandar Lampung. The results showed that 60.1% of patients had high level of satisfaction; 20.08% had moderate level of satisfaction; and 19.32% had low level of satisfaction. In conclusion, the majority of patients who received dental treatment at Puskesmas Kampung Sawah had high level of satisfaction of the services provided.Keywords: patient satisfaction; COVID-19; patient satisfaction questionnaire; dental services Abstrak: Kepuasan pasien merupakan suatu perbandingan antara persepsi pasien terhadap pelayanan yang diterima dengan harapan sebelum mendapatkan pelayanan. Tingkat kepuasan pasien sangat penting karena dapat menjadi tolak ukur keberhasilan suatu fasilitas pelayanan kesehatan. Pandemi COVID-19 memiliki dampak terhadap kepuasan pasien akibat adanya alur pelayanan yang berubah. Penelitian ini bertujuan untuk mengetahui gambaran tingkat kepuasan pasien terhadap pelayanan kedokteran gigi pada masa pandemi COVID-19. Jenis penelitian ialah observasional deskriptif dengan desain potong lintang. Penelitian ini dilakukan dengan menyebarkan patient satisfaction questionnaire kepada 100 pasien yang menerima perawatan kedokteran gigi di Puskesmas Kampung Sawah, Kecamatan Tanjung Karang Timur, Bandar Lampung. Hasil penelitian mendapatkan 60,01% pasien memiliki tingkat kepuasan tinggi; 20,08% memiliki tingkat kepuasan sedang; dan 19,32% memiliki tingkat kepuasan rendah. Simpulan penelitian ini ialah mayoritas pasien yang menerima perawatan kedokteran gigi di Puskesmas Kampung Sawah memiliki tingkat kepuasan yang tinggi terhadap pelayanan yang diberikan.Kata kunci: kepuasan pasien; COVID-19; patient satisfaction questionnaire; pelayanan kedokteran gigi